2006
DOI: 10.1017/s0003055406062289
|View full text |Cite
|
Sign up to set email alerts
|

Handling and Manhandling Civilians in Civil War

Abstract: T he toll of civil conflict is largely borne by civilian populations, as warring factions target noncombatants through campaigns of violence. But significant variation exists in the extent to which warring groups abuse the civilian population: across conflicts, across groups, and within countries geographically and over time. Using a new dataset on fighting groups in Sierra Leone, this article analyzes the determinants of the tactics, strategies, and behaviors that warring factions employ in their relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(242 citation statements)
references
References 37 publications
8
226
2
6
Order By: Relevance
“…Humphreys and Weinstein showed, for instance, in their analysis of Sierra Leonean factions that the higher level of indiscipline permitted inside the armed factions, the greater the perpetrated abuses outside the faction. 34 This is also confirmed by Weinstein. 35 He argues that a rebel group's access to easily accruable income, for example, from lootable natural resources such as drugs, are central in shaping the organizational structure of the movement and its strategies regarding treatment of noncombatants: it makes the organization more violent.…”
supporting
confidence: 65%
“…Humphreys and Weinstein showed, for instance, in their analysis of Sierra Leonean factions that the higher level of indiscipline permitted inside the armed factions, the greater the perpetrated abuses outside the faction. 34 This is also confirmed by Weinstein. 35 He argues that a rebel group's access to easily accruable income, for example, from lootable natural resources such as drugs, are central in shaping the organizational structure of the movement and its strategies regarding treatment of noncombatants: it makes the organization more violent.…”
supporting
confidence: 65%
“…In particular, fragmentation within a community can turn violence inward as factions terrorize civilians as a means to control the population they claim to represent and to punish those that support competing factions (Humphreys and Weinstein 2006;Kalyvas 2006;Weinstein 2007). In Southern Sudan, for instance, a split in the main rebel group, the Sudan People's Liberation Army, triggered a fratricidal war between southerners as the factions targeted their rivals' supporters.…”
Section: Violence Against Co-ethnic Civiliansmentioning
confidence: 99%
“…A closely-related topic in the security and conflict literature addresses how the presence of multiple VNSAs competing for power can have a negative impact on the local security environment (see e.g. Kalyvas 2006;Humphreys & Weinstein 2006;Balcells 2010;Hoover Green 2011). However, recent field research has found that non-state actors are not necessarily in competition against each other.…”
Section: Research On Political Authority Among Non-state Actorsmentioning
confidence: 99%